Forme di intenzionalità collettiva nella Sindrome di Asperger e nella schizofrenia: Una proposta fenomenologica - Bizzari, Valeria (B@belonline, 2022)
Asperger’s syndrome (AS) or high functioning autism is usually associated with brain deficits or behavioral disturbances, and the difficulties with crucial aspects of sociality encountered by patients with AS remain largely unexplored, leading to inadequate theories and, often, to inadequate treatment. The main aim of my paper is to understand this disorder through the lens of collective intentionality. For this reason, I will take into account the contemporary philosophical debate and I will also compare Asperger’s case with another disorder which involves a social, emotional detachment: schizophrenia. Trying to figure out the different levels of collective intentionality at stake in these two pathologies will be helpful not only in understanding and differentiating them, but also in better comprehending the structures of sociality themselves.